Urban frontiers in the global struggle for capital gains - Peter Mörtenböck; Helge Mooshammer (Finance and Society, 2018)
This article examines different ways in which finance models have become the ruling mode of spatializing relationships, arguing that the ongoing convergence of economic and spatial investment has transformed our environments into heavily contested ‘financescapes’. First, it reflects upon architecture's capacity to give both material and symbolic form to these processes and considers the impacts this has on the emergence of novel kinds of urban investment frontiers, including luxury brand real estate, free zones, private cities, and urban innovation hubs. Focusing on speculative urban developments in Morocco and the United Arab Emirates, the article then highlights the performative dimension of such building programs: how architectural capital is put to work by actively performing the frontiers of future development. Physically staking out future financial gains, this mode of operation is today becoming increasingly manifested in urban crowdfunding schemes. We argue that, far from promoting new models of civic participation, such schemes are functioning as a testbed for speculation around new patterns of spatial production in which architecture acts less as the flagstaff of capital than as a capital system in itself.